OVER VIEW OF THE USE OF INCENTIVES FOR SOIL AND WATER CONSERVATION SCHEMES - Das, D.C.; Singh, Shamsher (Journal of Soil and Water Conservation, 2022)
The evolution and growth of soil and water conservation over the past half a century has shown multiple-dimensions to combat degradation, low productivity and lack of employment and income opportunities. The growth also confirmed that watershed approach has become a unit for project planning for development of natural resources and utilising goods and services from the same. However, schemes launched over decades by various States and Central Government have used the concept and incorporated measures in the programme in different combinations to achieve their sectoral objectives. This diverse pathways of its development revealed five different factors which have influenced the grant of incentives. Considering the socio-economic backdrop the forms of incentives have also differed under different implementing Ministries on the basis of castes or economic categories of farming families. The pattern also differed from scheme to scheme. Incentives are given to individuals, communities, institutes, agencies and even to State Governments. Keeping these diversities the incentives for each Ministry and for different schemes have been discussed separately and provided in this write up for easy comparison and collateral examination. The gains and gaps have been illustrated through case studies. identified States where diversities could be easily perceived. Finally the impact of incentives have been identified in terms of ease with which projects could be implemented and participation of the people could be achieved. It was also brought out that in many cases soil and water conservation measures have been used as incentives to promote specific activities such as afforestation, pasture development, group action etc. An important observation has been the loss of effect of incentives after the project withdrawal specially in cases of externally supported programmes. The partnership between the grass-root level organizations and the implementing Department institutes should continue even after the project withdrawal and should be available to the departments for dialogue and collaboration from time to time. The partnership developed during implementation of project should persist as the protection, conservation, development and utilisation of products and services from natural resources base will continue to be the joint responsibility. This could be achieved by maintaining a sequential linkages and continuity in planning processes and appropriate pre-project and post project linkages between nationally and internationally supported projects.